The Comedies of Terence - Graves, Robert (Taylor and Francis, 2008)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- FOREWORD -- THE FAIR ANDRIAN -- THE MOTHER-IN-LAW -- THE SELF TORMENTOR -- THE EUNUCH -- THE TRICKS OF PHORMIO -- THE BROTHERS.